Subsequent Surgery after Revision Anterior Cruciate Ligament Reconstruction: Rates and Risk Factors from a Multicenter Cohort. Issue 7 (18th July 2016) - Ding, David; Group, Mars
Objectives: Failure or reinjury after anterior cruciate ligament (ACL) reconstruction can lead to recurrent instability and concomitant intra-articular injuries. While revision ACL reconstruction (rACLR) can be performed to restore knee stability and improve patient activity level, outcomes after these surgeries are reported to be inferior to primary ACL reconstruction. Further reoperation after rACLR can have an even more profound effect on patient satisfaction and outcome. Yet, there is a current lack of information regarding the rate and risk factors for subsequent surgery after rACLR. Methods: 1205 patients who underwent rACLR were enrolled between 2006 and 2011, comprising the prospective cohort. Two-year questionnaire follow-up was obtained on 989 (82%), while telephone follow-up was obtained on 1112 (92%). If a patient reported having a subsequent surgery, operative reports detailing the subsequent procedure(s) were obtained and categoriezed. A repeated meaures ANOVA was used to reveal significatnt differences in patient reported outcomes. Multivariate regression analysis was performed to determine independent risk factors for reoperation. Results: One hundred and twenty-two patients (10.1%) underwent a total of 172 subsequent procedures on the ipsilateral knee at 2-year follow-up. Of the reoperation procedures, 26.7% were meniscus procedures (69% meniscectomy, 26% repair), 18.6% were subsequent rACLR, 17.4% were cartilage procedures (61% chondroplasty, 17% microfracture, and 13% mosaicplasty), 10% hardware removal, and 9.3% were procedures for arthrofibrosis such has lysis of adhesions and synovectomy. Patients who had reoperations had significantly lower IKDC, KOOS symptoms and pain scores, and WOMAC stiffness scores at two-year follow up. Multivariate analysis revealed that patients under 20 years old were 2.1 times more likely than patients aged 20-29 to have a reoperation. Use of allograft at the time of rACLR and staged revision (bone grafting of tunnels before rACLR) were also significant predictors for need for reoperation within 2 years. Patients with grade IV cartilage damage seen during rACLR were 47% less likely to undergo subsequent operations within 2 years. Gender, BMI, smoking history, Marx activity score, technique for femoral tunnel placement and meniscal tear or meniscal treatment at the time of rACLR showed no significant effect on reoperation rate. Conclusion: There is a significant reoperation rate following rACLR at two years (10.1%). The most prevalent reoperations involved meniscal procedures. Independent risk factors for subsequent surgery on the ipsilateral knee include age<20 years old, a staged revision and use of allograft tissue at the time of rACLR.